Is aloe vera effective for wound healing? The state of the art - Azevedo, Juliana Santos de Jesus; Juliao, Erielma Lomba Dias; Dantas, Juliana Borges de Lima; Reis, Júlia Vianna Neri Andrade (Journal of Oral Diagnosis, 2019)
Introduction: Aloe vera is a herbal plant that has been used widely for centuries as a natural medicine. Its therapeutic activity is based on the numerous beneficial pharma- cological properties induced by the parenchyma. It is easy to access, manipulate and is low-cost; these properties have led to a progressive increase in its consumption. However, its action in the cicatricial process is not fully known, which has driven research into new discoveries in this context. Aim: The purpose of this literature narrative review was to discuss the current information available on the benefits of using Aloe vera in the wound healing process. Materials and methods: Scientific articles were selected from the Pub- Med and LILACS databases between February 2018 and July 2018, by using the English and Portuguese words of “Aloe Vera”, “Wound healing”, “Healing” and “Tissue repair”. In total, 229 articles were found in PubMed and 63 articles were found in LILACS. After reading the abstracts, 30 articles that reported how the pharmacological properties of Aloe vera influence the healing process were selected. Results: Aloe vera exerted positive effects on the treatment of oral ulcers and protection of the mucous membranes, with reductions in these lesions and the painful symptomatology. In addition, it was effective for the prevention and treatment of oral mucositis and the reduction of candidiasis in patients with cancer. Promising results have also been reported from the treatment of symptomatic oral lichen planus. In the treatment of plaque-induced gingivitis, Aloe vera provided a significant improvement in inflammation. Final considerations: The literature supports the anti-inflammatory and cicatricial potential of Aloe vera, which has a wide indication for the treatment of several conditions. Therefore, additional clinical studies based on scientific evidence are needed to gain a better understanding of Aloe vera, its compounds and therapeutic indications.